2009
DOI: 10.1080/10428190903060095
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and laboratory characterization of a large cohort of patients with Castleman disease retrospectively collected from a single center

Abstract: The clinical, pathological treatment, and prognostic data of 55 patients with Castleman disease (CD) were collected retrospectively from a single medical center. Thirty-four cases were classified as uni-centric; the remaining 21 cases were diagnosed as multi-centric CD. Regarding pathological classification, 38 cases were hyaline vascular type, account for 69.1% of all patients. Nine cases were diagnosed as plasmacytic type and eight cases as mixed cellularity type. Several prominent clinical complications wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 32 publications
2
21
0
2
Order By: Relevance
“…Several series have characterized CD clinical manifestations and histopathology (Dong et al , ; Liu et al , ; Robinson et al , ). A meta‐analysis of 416 CD patients from the literature found that centricity, pathology type, the presence of symptoms, gender and age all predict outcome in univariate analyses (Talat & Schulte, ).…”
mentioning
confidence: 99%
“…Several series have characterized CD clinical manifestations and histopathology (Dong et al , ; Liu et al , ; Robinson et al , ). A meta‐analysis of 416 CD patients from the literature found that centricity, pathology type, the presence of symptoms, gender and age all predict outcome in univariate analyses (Talat & Schulte, ).…”
mentioning
confidence: 99%
“…Paraneoplastic pemphigus may concern <10% of cases, associated with adverse outcome mainly due to mucous membrane involvement (11). In our series, pemphigus was present in two cases, associated with bronchiolitis and risk of transient postoperative worsening of the dyspnea and broncho-pleural fistula in case of lung resection.…”
Section: Surgical Managementmentioning
confidence: 74%
“…15,16 La coexistencia con enfermedades autoinmunes ha sido poco reportada en la literatura médica. En la publicación de Ginebra y cols en 2004, se detalló la asociación con ciertas enfermedades autoinmunes (tabla), siendo su variedad de células plasmática y mixta como la más frecuente en esta serie, y el lupus eritematoso sistémico, enfermedad mixta de tejido conectivo, miastenia gravis y síndrome de Sjögren como las más frecuentes.…”
Section: Discussionunclassified
“…17 En ciertas publicaciones se detalla la correlación y posibles complicaciones existentes entre la enfermedad de Castleman y otras entidades patológicas como el síndrome POEMS, pénfigo paraneoplásico, enfermedad de Hodking, pseudo tumor pancreático, sarcoma de células dendríticas, miastenia gravis, síndrome nefrótico, bronquiolitis obliterante, anemia autoinmune, enfermedad de Still del adulto, síndrome de sjogren, entre otras. 2,15,23,24,25 Es de mencionar que parte de los criterios menores asociados al síndrome de POEMS, se presentan en la enfermedad de Castleman, por lo que es importante su diagnóstico diferencial. 26 En nuestro caso, la coexistencia de polimiositis y enfermedad de Castleman no está del todo claro, ya que existe muy poca información en la literatura médica referente a estas dos enfermedades juntas, como se observa en el trabajo de De Marchi y cols en el que exponen coexistencias entre la enfermedad de Castleman y enfermedades reumatológicas, donde se reporta a la polimiositis como un único caso asociado con la enfermedad de Castleman de localización multicéntrica.…”
unclassified